ANALISIS KELAYAKAN USAHATANI TEMBAKAU (Nikotiana Tabacum L.) Di KECAMATAN MUNTILAN KABUPATEN MAGELANG - Nur Rosyidah (Fakultas Pertanian UST, 2017)
This study aims to determine the effect of production, land area, price, and use of seeds, fertilizers and pesticides on tobacco farming income in Muntilan district Magelang District, as well as analyzing whether tobacco farming in Muntilan district of Magelang regency worth the effort. The basic method used in this research is descriptive. Engineering study is a survey research techniques. Data analysis method used is the analysis of income, non-linear regression analysis, statistical testing, and feasibility analysis (R / C ratio). The survey results revealed that: (1) at the 95% confidence level independent variables include variables of production, land area, price, use of seeds, fertilizers and pesticides simultaneously significant effect (significant) on the dependent variable that farm income of tobacco in the district Muntiln Magelang District , with a coefficient of determination of 84.8%. (2) Several independent variables include production variables with a regression coefficient of 2.832; variable land area with a regression coefficient of -0.665; price variable with significant regression coefficient of 2.051 (significant) against the tobacco farm income. (3) Variable seed with a regression coefficient of 0.094; variable regression coefficient -0.338 fertilizer and pesticide variable with regression coefficient of -0.556 no significant effect (not significant) against the tobacco farm income. (4) Based on analysis of the feasibility of farming R / C ratio is worth 2,498, concluded that tobacco farming in Muntilan district of Magelang regency worth the effort.Keywords: farming, tobacco, income, eligibility